Pengembangan Sistem Informasi Monitoring Pengelolaan Dana Bantuan Operasional Sekolah berbasis Website Studi Kasus : Korwilcam Bidang Pendidikan Kecamatan Sempor - Arief Widiyatmoko; Satrio Agung Wicaksono; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Education is the right of all Indonesian without exception. The government is obliged to guarantee the implementation of education at the basic level, therefore the government has launched a program called BOS (‘Bantuan Operasional Sekolah'). In its implementation, schools are required to make an accountability report for the use of BOS funds in accordance with government regulations from the education and culture office regarding technical guidelines for the use of BO funds. In reporting the use of BOS funds, several obstacles were encountered, namely frequent delays in reporting which caused the regional coordinator to recap data to be hampered, so that the purpose of this study was to build an information system that could monitor schools so that reports on the use of BOS funds to be more controlled. System development is carried out using the waterfall model. In this study, the problem can be overcome by changing the current business process into a recommendation business process so as to produce functional requirements that will be implemented on a website-based information system whose design uses an object-oriented approach which will be implemented in the system using the PHP framework, CodeIgniter. After the information system built is valid according to user needs, then testing is carried out using user acceptance testing so that the user acceptance index of the system being built is known. Based on this test, the results show that the user accepted the information system and the features in it.